2020
DOI: 10.37829/hf-2020-da03
|View full text |Cite
|
Sign up to set email alerts
|

The long-term impacts of New Care Models on hospital use: An evaluation of the Integrated Care Transformation Programme in Mid Nottinghamshire

Abstract: This report presents the findings of an evaluation of the long-term impacts of the Mid-Nottinghamshire Better Together Integrated Care Transformation Programme (ICTP) over a 6-year period from its launch in April 2013 until March 2019. The programme was established by Mansfield and Ashfield clinical commissioning group (CCG) and Newark and Sherwood CCG, together with local partners. In March 2015, the Mid-Nottinghamshire Better Together programme achieved vanguard status as an integrated primary and acute care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…Table 2 Comparison of significant pilot experiences and outcomes (extracted from publications of the national evaluation teams and selected studies) [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Key Themes Identified Through Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 Comparison of significant pilot experiences and outcomes (extracted from publications of the national evaluation teams and selected studies) [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Key Themes Identified Through Evaluationmentioning
confidence: 99%
“…It is also notable that a longer-term evaluation of one Vanguard site found that a lower rate of increase in a range of measures of unplanned hospital care towards the end of a six-year period of pilot operation. The evaluators hypothesised that they may have captured the impact of sustained improvements to community care on hospital usage which may be missed in shorter periods of analysis [12].…”
Section: What Did the Pilot Programmes Achieve?mentioning
confidence: 99%
See 1 more Smart Citation
“…Future evaluations of large-scale service change should continue to consider such a multifaceted approach but perhaps with less prescription of what should be explored in depth at the local level. In the evaluation of the New Models of Care Vanguard programme, the ability to deliver robust counterfactual analysis has been limited to the national-level evaluation teams [ 24 – 26 ]. Given the apparent challenges faced by local evaluation teams in trying to deliver counterfactuals (under resource constraints and limited time horizons), there is an argument that local analysis should focus on providing causal explanations for impact in a given context.…”
Section: Discussionmentioning
confidence: 99%
“…It may take time for changes to the system to translate into improvements for patients. For instance, a recent study into an integrated care transformation programme 32 shows that despite an initial increase of hospital activity, it took 6 years for the integrated care initiative to deliver a reduction of both A&E attendances and emergency admissions.…”
Section: Discussionmentioning
confidence: 99%